Development of a community-based COVID-19 intervention in rural Ghana: a document analysis - Shadrack Osei Frimpong; Moro Seidu; Sam Kris Hilton; Yusuf Ransome; Elijah Paintsil; Kristina Talbert-Slagle; Sharon Dorcoo-Attipoe; Carol Brayne (BMC, 2022)
Abstract Background The COVID-19 pandemic has caused the loss of millions of lives and economic breakdowns in many countries across the globe. Despite the limited availability of vaccines and the challenges of poor health infrastructure, few interventions have been developed and implemented for those who live in rural areas, particularly in sub-Saharan Africa. In response, Cocoa360, a global health nonprofit in rural Ghana designed an intervention called Cocoa360's COVID-19 Preparedness and Outbreak Prevention Plan (CoCoPOPP). This paper aimed to examine the extent to which CoCoPOPP's design aligned with the Promoting Action on Research Implementation in Health Services (PARIHS) framework. Methods We reviewed documents influencing CoCoPOPP's design between March and June 2021. A total of 11 documents were identified for analysis. Using the Promoting Action on Research Implementation in Health Services (PARIHS) framework as a guide, thematic analysis was done to analyze the extracted data. Results Overall, CoCoPOPP's design aligned with the evidence, context, and facilitation domains of the PARIHS framework. It positioned CoCoPOPP as an intervention that considered the unique context of a rural Ghanaian setting. It was guided by robust and high-quality published and non-published evidence and engaged external and internal stakeholders during its implementation. CoCoPOPP's context-dependent nature positions it for potential replication in sub-Saharan Africa's rural communities with similar farming contexts. Specific areas that were less well and/or not addressed were the unintended negative consequences of community engagement, the absence of primary data in the guiding evidence, and the lack of a facilitation continuum coupled with the role of power during the facilitation process. Conclusion CoCoPOPP, Cocoa360's response to the COVID-19 pandemic in rural Ghana, is an evidence-driven, context-dependent public health intervention that has been designed to reduce COVID-19 infections and prevent potential deaths. This study underscores the importance of considering the unique community and cultural contexts, employing evidence, and engaging local and external actors as facilitators when designing interventions to respond to global health pandemics.